Membangun Pendidikan Islam Yang Unggul, Berdaya Saing Tinggi, Dan Berakhlak Mulia Berlandaskan Kurikulum Cinta Untuk Menghasilkan Generasi Bangsa Berkompeten - Nur Rahmawati (Sipakatau: Jurnal Pendidikan dan Kebudayaan, 2026)
Islamic education plays a strategic role in shaping a generation that is not only intellectuallysuperior but also morally and spiritually strong. The challenges of globalization,technological advancement, and the values crisis demand that Islamic education transforminnovatively and be highly competitive without abandoning noble moral values. This articleaims to examine the concept of developing superior and competitive Islamic educationthrough the implementation of the Love Curriculum as a learning foundation. The methodused is a literature study with a qualitative-descriptive approach, drawing on variousscientific sources, educational policies, and the thoughts of Islamic educational figures. Theresults of the study indicate that the Love Curriculum, which emphasizes the values ofcompassion, empathy, tolerance, and responsibility, can strengthen students' character whileenhancing academic competence and 21st-century skills. The implementation of the LoveCurriculum in Islamic education contributes significantly to producing a competent,globally competitive, and noble generation.